A Novel Mutation in Lamin A/C Gene: Phenotype and Consequences on the Protein Structure and Flexibility. (3rd March 2010) - Carboni, Nicola; Floris, Matteo; Valentini, Maria; Marrosu, Giovanni; Cocco, Eleonora; Maioli, Maria Antonietta; Solla, Elisabetta; Mateddu, Anna; Mura, Marco; Marrosu, Maria Giovanna
Abstract : Laminopathies are a heterogeneous group of LMNA gene alteration-related disorders including muscular dystrophies, peripheral neuropathies, progeria, lipodystrophies, mandibuloacral dysplasia and restrictive dermopathy. We recently identified a family displaying mild skeletal muscle compromise and contractures and complaining of cardiac symptoms associated to a novel mutation consisting in c.388 G/T exon 2 LMNA gene substitution. The aim of the study was to assess the pathogenic effect of this mutation by means of computational experiments. The c.388 G/T mutation is a missense mutation causing the substitution of the amino acid Alanine with Serine in position 130 of the protein sequence of the coiled-coil region of Lamin A rod domain. Computational predictions and molecular dynamic simulation of lamin filaments revealed a 50% reduction in the probability of the sequence adopting a coiled-coil conformation. The present study provides a feasible explanation for the potential pathogenic effect of the novel c.388 G/T exon 2 LMNA gene mutation. The simulation revealed how the mutation alters the flexibility of lamin filaments and likely determines an impairment in the constitution of the coiled-coil structure.